Hubungan Pengetahuan Dengan Perilaku Penderita Hipertensi Terhadap Cara Pengobatan Hipertensi Dengan Terapi Komplementer Di Puskesmas 1 Denpasar Timur - sutini, ni kadek; Dewi, Putu Ayu Laksmi; Suyasa, I Gede Putu Darma; Sanjana, I Wayan Edi (JURNAL MEDIKA USADA, 2024)
Background: Non-pharmacological management of hypertension through complementary medicine has now been developed in Indonesia. However, the interest of hypertensive patients in complementary medicine is not optimal because there are many factors that influence the behavior of patients in the use of complementary medicine. Methods: This study employed an analytic study design with a cross-sectional approach. This research was conducted at Puskesmas 1 East Denpasar for 1 month. This study involved 101 hypertensive patients using accidental sampling technique. Data collection was carried out using a questionnaire. Data were analyzed univariately and bivariately using SPSS version 20. Results: This study showed that most hypertensive patients had good knowledge of hypertension treatment with complementary therapies (64.4%). A total of 53.5% of hypertensive patients showed adequate behavior in the treatment of hypertension with complementary therapy. Based on the chi square test, it was found that there was a significant relationship between knowledge and behavior of hypertensive patients towards hypertension treatment with complementary therapy (p-value = 0.04). Conclusion: It is recommended for health workers to increase education and promotion about hypertension treatment with complementary therapy, especially for hypertensive patients with poor knowledge.